2015
DOI: 10.1007/s11745-015-4104-y
|View full text |Cite
|
Sign up to set email alerts
|

Isoprenoid Alcohols are Susceptible to Oxidation with Singlet Oxygen and Hydroxyl Radicals

Abstract: Isoprenoids, as common constituents of all living cells, are exposed to oxidative agents—reactive oxygen species, for example, singlet oxygen or hydroxyl radicals. Despite this fact, products of oxidation of polyisoprenoids have never been characterized. In this study, chemical oxidation of isoprenoid alcohols (Prenol-2 and -10) was performed using singlet oxygen (generated in the presence of hydrogen peroxide/molybdate or upon photochemical reaction in the presence of porphyrin), oxygen (formed upon hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Furthermore, a study showed that short-and long-chain polyisoprenoid alcohols are prone to thermo-oxidation, and it has been speculated that oxidized isoprenoids might be formed in the cells because of chemical processes driven by oxidative agents (e.g., reactive oxygen species) [54]. This hypothesis has recently been substantiated by experimental data indicating the susceptibility of polyisoprenoid alcohols to various oxidizing agents for the first time [55]. Yet, the full mechanisms of dolichol oxidation have to be clarified further.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, a study showed that short-and long-chain polyisoprenoid alcohols are prone to thermo-oxidation, and it has been speculated that oxidized isoprenoids might be formed in the cells because of chemical processes driven by oxidative agents (e.g., reactive oxygen species) [54]. This hypothesis has recently been substantiated by experimental data indicating the susceptibility of polyisoprenoid alcohols to various oxidizing agents for the first time [55]. Yet, the full mechanisms of dolichol oxidation have to be clarified further.…”
Section: Discussionmentioning
confidence: 97%
“…Several terpenic compounds had been previously reported in blueberry fruits, namely linalool, linalool oxide, and α-terpineol, were identified (Beaulieu, Stein-Chisholm, & Boykin, 2014; Du & TA B L E 3 Concentration of major volatile compounds (C) detected and quantified by GC-FID in blueberry wines after alcoholic fermentation by the yeast strain Saccharomyces cerevisiae QA23 in laboratory-scale fermentations (LabSFs) and midscale fermentations (MSFs) or after 16 months in bottle Rouseff, 2014; Farneti et al, 2017). Among these compounds, β-citronellol concentration decreased significantly during aging and is believed to be correlated with the degradation of this compound because it is prone to oxidation by light or hydrogen peroxide (Komaszylo née Siedlecka et al, 2016). The linalool concentration decreased significantly during aging, probably due to chemical phenomena, especially oxidation reactions.…”
Section: Minor Volatilesmentioning
confidence: 99%
“…Additional terpenic compounds such as transcarveol, β-citronellol, and p-1-menthen-9-ol were found in blueberry wines, but these compounds can also originate from the fruit due to its terpenoid composition. Among these compounds, β-citronellol concentration decreased significantly during aging and is believed to be correlated with the degradation of this compound because it is prone to oxidation by light or hydrogen peroxide (Komaszylo née Siedlecka et al, 2016).…”
Section: Minor Volatilesmentioning
confidence: 99%
“…Recently, cis-polyisoprenoids gained special attention due to several breakthroughs in the field including improvements in the analytical techniques for their analysis 17,18 , partial identification of their enzymatic machinery 19 , and the discovery of new biological functions beyond glycosylation 20,21 . Among some of these biological functions are the regulation of the membrane fluidity 21 , stimulation of spore wall formation in yeast 20 , and scavenging free radicals in cell membranes [22][23][24] . Interestingly, in cancer cells 25 and P. falciparum 26 , protein dolichylation occurs as a post-translational event, but functions of such derivatives and enzymes involved in this posttranslational protein lipid modification remain unknown.…”
mentioning
confidence: 99%